Retinoblastoma genetics screening and clinical management - Himika Gupta; Sivasankar Malaichamy; Ashwin Mallipatna; Sakthivel Murugan; Nallathambi Jeyabalan; Vishnu Suresh Babu; Anuprita Ghosh; Arkasubhra Ghosh; Sam Santhosh; Somasekar Seshagiri; Vedam L. Ramprasad; Govindasamy Kumaramanickavel (BMC, 2021)
Abstract Background India accounts for 20% of the global retinoblastoma (RB) burden. However, the existing data on RB1 gene germline mutations and its influence on clinical decisions is minimally explored. Methods Fifty children with RB underwent complete clinical examination and appropriate multidisciplinary management. Screening of germline RB1 gene mutations was performed through next-generation sequencing and Multiplex Ligation-dependent Probe Amplification (MLPA) analysis. The mutation and non-mutation groups were compared for clinical parameters especially severity, progression and recurrence. Results Twenty-nine patients had bilateral RB (BLRB) and 21 had unilateral RB (ULRB). The genetic analysis revealed 20 RB1 variations in 29 probands, inclusive of 3 novel mutations, known 16 mutations and heterozygous whole gene deletions. The mutation detection rate (MDR) was 86.2% in BLRB and 19% in ULRB. Associations of disease recurrence (p = 0.021), progression (p = 0.000) and higher percentage of optic nerve invasion, subretinal seeds and high-risk pathological factors were observed in the mutation group. Clinical management was influenced by the presence of germline mutations, particularly while deciding on enucleation, frequency of periodic follow up and radiotherapy. Conclusions We identified novel RB1 mutations, and our mutation detection rate was on par with the previous global studies. In our study, genetic results influenced clinical management and we suggest that it should be an essential and integral component of RB-care in India and elsewhere.